HUBUNGAN ANTARA KECERDASAN SPIRITUAL DENGAN PROKRASTINASI PADA MAHASISWA TINGKAT AKHIR - Ekawaty Rante Liling; Firmanto Adi Nurcahyo; Karin Lucia Tanojo (Universitas Ahmad Dahlan, 2013)
AbstractProcrastination can occur to university students especially in finishing final papers. Procrastination is a behavior detrimental to oneself and others that associate with lack of ability to manage themselves. The ability of self-management is part of how someone judges and values every actions and that involve spiritual intelligence. This study examines the relationshipbetween spiritual intelligence and procrastination behavior of students who do the final paper. This research involved 62 students at the Universitas Pelita Harapan Surabaya. Spiritual intelligence scale and procrastination scale were used to collect the data. Results show there is a significant negative correlation between spiritual intelligence and procrastination (r = -0.307, p = 0.008, p <0.01). The higher spiritual intelligence level, the lower procrastination behavior will be and vice versa. Spiritual intelligence would lead someone to decide on appropriate actions and think about the consequences of his/her actions. Students who have high spiritual intelligence would tend to avoid procrastination behavior that disserving themselves and others.Keywords: final paper; procrastination;spiritual intelligence